2018
DOI: 10.17352/2455-2976.000072
|View full text |Cite
|
Sign up to set email alerts
|

Troponin Levels in Patients in Acute Phase of Stroke

Abstract: Background and Purpose: The purpose of this study was to assess the correlation of cTn levels in the acute phase of ischemic stroke with the extent of stroke, the degree of disability assessed on the modifi ed Rankin Scale, and their prognostic signifi cance. Methods: Patients were divided into 3 groups: (A) ischemic strokes, (B) ischemic strokes followed by hemorrhagic transformation, and (C) hemorrhagic strokes, excluding patients with symptoms of acute coronary syndrome. Cardiac troponin levels (cTn) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…9 While another study showed the opposite results, where 45% of study patients were male. 10 We also observed that about 58% of the study patients had right-sided weakness and 42% had left-sided weakness, indicating the involvement of the left side of the brain in AIS. Thus, in my present study, patients had more left-side brain involvement.…”
Section: Discussionsupporting
confidence: 55%
“…9 While another study showed the opposite results, where 45% of study patients were male. 10 We also observed that about 58% of the study patients had right-sided weakness and 42% had left-sided weakness, indicating the involvement of the left side of the brain in AIS. Thus, in my present study, patients had more left-side brain involvement.…”
Section: Discussionsupporting
confidence: 55%
“…Seven studies were conducted in the United States [5] , [7] , [13] , [24] , [25] , [31] , [33] , two in Canada [22] , [23] , nine in Europe [4] , [10] , [12] , [20] , [21] , [26] , [27] , [29] , [32] , two in Australia [6] , [30] , and three studies in Asia [8] , [9] , [11] .…”
Section: Resultsmentioning
confidence: 99%
“…Although the correlation between cTn and comorbidity has been individually studied [4] , [5] , [6] , [8] , [10] , [11] , [12] , [13] , [14] , [20] , [35] , the possibility of simultaneous comorbidities is not clarified. Therefore, there is higher probability of selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation